Comparative Design Strategi Peningkatan Daya Saing Klaster Usaha Kecil Dan Menengah Pengolahan Kopi - Dayat, Mohammad; Sudarmiatin; Hermawan, Agus (Universitas Yudharta Pasuruan, 2022)
Indonesia is one of the largest coffee exporting countries in the world. Increasing the competitiveness of small and medium coffee industry clusters is a strategic issue that needs to be considered. The small and medium coffee industry in Indonesia can become a mainstay commodity for export to foreign countries. However, the small and medium coffee industry still has many obstacles, including low human resources capabilities, difficulty in penetrating access to capital, and low levels of technology adoption. This study was conducted to determine the strategy model for increasing the competitiveness of relevant small and medium industry clusters of coffee processing. One methodological approach alone is not enough to strive to increase the competitiveness of the small and medium coffee industry in Indonesia. Comparing strategic management is a choice of an alternative approach to able to increase optimal competitiveness. By comparing the structural equation model and SWOT analysis, it is hoped that the right program recommendations will be found to increase the competitiveness of the sustainable small and medium coffee industry.